2015
DOI: 10.5455/msm.2015.27.75-78
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cystatin C - Marker of Inflammation and Cardiovascular Morbidity in Chronic Kidney Disease Stages 1-4

Abstract: Aim:The aim of the research was to compare the relationship between inflammatory biomarkers and procoagulants with kidney function assessed by using cystatin C, serum creatinine, and eGFR and determine the sensitivity of cystatin C, serum creatinine and eGFR to total cardiovascular morbidity in patients with CKD stages 1-4.Methods:The research included 120 patients older than 18 years with CKD stages 1-4 monitored over a period of 24 months.Results:Serum cystatin C correlates with fibrinogen (p<0.01), serum al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 20 publications
0
18
0
2
Order By: Relevance
“…Cystatin C is a protein associated with inflammation. 83 Additionally, CSF cystatin C levels have previously been shown to correlate with pain status, 44, 67 although this idea has been at the center of some controversy. 31 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cystatin C is a protein associated with inflammation. 83 Additionally, CSF cystatin C levels have previously been shown to correlate with pain status, 44, 67 although this idea has been at the center of some controversy. 31 …”
Section: Resultsmentioning
confidence: 99%
“…Cystatin C was chosen because the initial proteomics screen determined that it was increased in both symptomatic and asymptomatic DD and because of its association with inflammation. 83 In addition, cystatin C was previously proposed as a putative CSF biomarker for pain, 44, 67 although this claim is controversial. 31 Hemopexin was selected because the initial proteomic screen found that it was significantly increased in painful DD, but not pain-free DD.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, elevated circulating ADMA concentrations and thus a reduced NO production are early forerunners of CKD, and may precede other diagnostic signs like the reduction of GFR [37]. Furthermore, cystatin C was found to be a marker not only of renal function but also of inflammation, as associations between cystatin C and proinflammatory cytokines like TNFα were detected [38]. Interestingly, serum creatinine concentrations and eGFR showed no association with this cytokine [38].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, cystatin C was found to be a marker not only of renal function but also of inflammation, as associations between cystatin C and proinflammatory cytokines like TNFα were detected [38]. Interestingly, serum creatinine concentrations and eGFR showed no association with this cytokine [38]. TNFα is a trigger for exocytosis of Weibel-Palade bodies [1, 39, 40].…”
Section: Discussionmentioning
confidence: 99%
“…The level of cystatin C is reported to be strongly correlated with inflammatory cytokine levels, blood pressure and blood coagulation factor tendency. 19 21 In addition, cystatin C serves as a predictive biomarker of cardiovascular events. 22 This suggests that cystatin C is not only a sensitive early predictor of kidney dysfunction, but also a powerful marker of cardiovascular disease.…”
mentioning
confidence: 99%